Editor's Notes - Verbuč, David (Lidé města, 2020)
I took over the editorial duties of the English editions of the Lidé města / Urban People journal in January 2020 (I am thankful to the former editor, Hedvika Novotná, for managing the English editions for the previous 12 years). I am dedicated to the high-quality standards of the journal, and to its ethnographic specificity, as well as to its wide international and interdisciplinary outreach. We have followed a rigorous selection and revision process for the articles published in this edition, and the positive outcome resulting from these efforts should be apparent to the readers. I want to express my gratitude here to all of the anonymous reviewers, as well as to my colleagues from the Lidé města / Urban People journal, who contributed to the successful completion of this issue.